2012
DOI: 10.1021/ml300079e
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Imidazoquinolines with Toll-Like Receptor 7/8 Independent Cytokine Induction

Abstract: Toll-like receptors (TLRs) are key targets in the design of immunomodulating agents for use as vaccine adjuvants and anticancer treatments. The imidazoquinolines, imiquimod and resiquimod, have been shown to activate TLR-7 and -8 which in turn induce cytokine production as part of the innate immune response. Herein, we report the synthesis and discovery of a C7-methoxycarbonyl derivative of imiquimod that stimulates cytokine production but is devoid of TLR-7/8 activity. Data is presented that shows this analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 16 publications
5
50
0
Order By: Relevance
“…The phagosome is an efficient platform for the recognition of diverse ligands, sometimes involving co-operative interactions between TLR8 and other TLRs [56], or even other classes of PRRs [57]. Additionally, our lab has previously shown that CL075 can also activate DCs via other classes of PRRs, such as the inflammasome [17], which is supported by reports that imidazoquinolines can trigger induction of inflammatory cytokines in the absence of TLR 7 or 8 agonist activity [58]. Lastly, using molecular modeling studies, Govindaraj et al demonstrated that the binding affinity of the TLR8 agonist R848 plays a key role in species-specificity [59].…”
Section: Discussionmentioning
confidence: 82%
“…The phagosome is an efficient platform for the recognition of diverse ligands, sometimes involving co-operative interactions between TLR8 and other TLRs [56], or even other classes of PRRs [57]. Additionally, our lab has previously shown that CL075 can also activate DCs via other classes of PRRs, such as the inflammasome [17], which is supported by reports that imidazoquinolines can trigger induction of inflammatory cytokines in the absence of TLR 7 or 8 agonist activity [58]. Lastly, using molecular modeling studies, Govindaraj et al demonstrated that the binding affinity of the TLR8 agonist R848 plays a key role in species-specificity [59].…”
Section: Discussionmentioning
confidence: 82%
“…Clinical trials of imiquimod were discontinued owing to its serious adverse side effects. [5] Imidazoquinoline analogues such as imiquimod, [6] resiquimod, [6] gardiquimod, [7] (1), [7] and 1-benzyl-2-butyl-1H-imidazo[4,5-c]quinolin-4-amine (2)a re all potent agonists of this pathway ( Figure 1A). Their ability to triggering remarkable levels of cytokinep roduction were revealed upon their conjugation with antigenst hat have weak immunogenicity.T his discovery demonstrated that TLR 7c an be activated by coupling an antigen to the terminal carboxyl group at N9 of the inactive ligand adenine analogues.…”
mentioning
confidence: 99%
“…[1][2][3] They respondu niversally to the presence of viral genomic ssRNA within the cytoplasm. [6][7][8]16] For the guaninea nalogues, SAR studies showedt hat analogues with thiazolo[4,5-d]pyrimidine [17] or pyrazolo[3,4-d]pyrimidine [18] ring systemsa re all active. [5] Imidazoquinoline analogues such as imiquimod, [6] resiquimod, [6] gardiquimod, [7] …”
mentioning
confidence: 99%
See 2 more Smart Citations